Mechanisms of heat-hydrodynamic instability with local heat supply to gas - Basok, B.I.; Gotsulenko, V.V. (Reports of the National Academy of Sciences of Ukraine, 2018)
A mathematical model of nonstationary gas motions with a local supply of heat to a gas along a certain surface is developed. In the equations of motion, the heat energy dissipation tensor associated with the heat supply surface and characterizing the presence of a negative thermal resistance is specified. An equation is obtained for the components of the given tensor, and some of its particular cases are considered.